Characterization of the primary metabolome during the long-term response to NaHCO3-derived alkalinity in Lotus japonicus ecotypes Gifu B-129 and Miyakojima MG-20 - Bordenave, César Daniel (2017)
This study compares the response of two ecotypes of the model species Lotus japonicas, MG-20 and Gifu-B-129, to soil alkalinity, in terms of plant survival and changes in global primary metabolome profiles. After 54ï¿½days of treatment with 30ï¿½mM NaHCO3, a higher survival was registered in MG-20, with respect to Gifu-B-129 plants. Gas chromatography–mass spectrometry (GC–MS) analysis of shoot extracts from both ecotypes yielded 123 different analytes, 62 of which were identified, including organic acids (OA), amino acids (AA), sugars and polyols. Glycolysis, TCA cycle and amino acids metabolism pathways were differently affected by alkalinity according to the ecotype. The lower tolerance of Gifu B-129 plants to 10ï¿½mM NaHCO3, compared with MG-20 ones could be related, at least partially, to the differential accumulation of phosphoric, lactic, threonic, succinic and p-coumaric acids, as well as β-alanine and valine.